THE STUDY OF SME'S PERFORMANCE IN FURNITURE CARVING INDUSTRY - Tri Siwi Agustina (Universitas Airlangga, 2021)
The center of SMEs carving furniture in Karduluk village, Sumenep Regency in Madura, East Java which has dynamic and uncertain environment and also high level of competition. Such situation needs adequate managerial capabilities so that SME players can sustain their existence from external competition. In spite of its thriving existence, the industry has some potential problems, which need to be identified The purpose of this research is to determine the effect of the entrepreneurship orientation, the capability of business network towards the performance of SMEs through the commitment of the businessmen. This research employed quantitative analysis, which used AMOS as its method of analysis. Data collection was conducted by distributing questionnaires to 105 craftman who were also managers of craving furniture units. This research found that businessmen orientation affected the performance of carving furniture. Business networking capability affected the performance of carving furniture. Behavioral commitment had a partial mediation impact on entrepreneurship orientation towards the performance of carving furniture. Behavioral commitment had a full mediation impact on entrepreneurship orientation towards the performance of carving furniture.